Prevention of road accidents due to drowsiness detection using PERCLOS algorithm - Srivastava, Devesh Kumar; Tiwari, Pradeep Kumar (Journal of discrete mathematical sciences & cryptography, 2021)
A Road traffic accident can be characterized as, 'An occasion that happens on a road open traffic; bringing about at least one person being damaged or murdered, wherein any event one moving vehicle is included. In this way, a road accident is a crash between vehicles; among vehicles and people on foot; among vehicles and creatures or vehicles, and geological or design deterrents. Every year, many road accidents occur due to the drowsiness transpired to the driver. Sleepy driving can be a hazard to any individual who gets in the driver's seat of a vehicle. It is the reason for at any rate 100,000 vehicle crashes every year. Subsequently, the primary thought behind this paper is to build up a non-meddling framework that can distinguish the languor of the driver and issue an auspicious cautioning to counteract the mishaps and thusly set aside cash and diminish individual anguish. This framework works by consistently observing the eyes of the driver and by utilizing the level of eyelid conclusion after some time (PERCLOS) calculation.